Method for preparing self-repairing polysilazane gel electrolyte at room temperature by in-situ polymerization method
By using Si-O bond-containing epoxy monomers or amine monomers to form a crosslinking network in lithium-ion batteries, a room-temperature, green and self-healing polysilamane gel electrolyte is prepared, which solves the problems of poor compatibility of traditional electrolytes and lacks self-healing properties, and achieves a more stable and safe operation of lithium-ion batteries.
Patent Information
- Application Number
- CN202411733131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Traditional liquid electrolytes have poor compatibility with lithium metal negative electrodes during the circulation of lithium-ion batteries, which can easily lead to problems such as lithium dendrites puncture diaphragm. The existing gel electrolytes lack self-healing and efficient in-situ polymerization capabilities.
The preparation method of self-healing polysilamane gel electrolyte that uses Si-O bond-containing epoxy monomers or amine monomers to form a crosslinking network with amine monomers and epoxy monomers to achieve in-situ polymerization. The method is carried out at room temperature, has the characteristics of green and environmental protection, and imparts the self-healing ability of the gel electrolyte through the dynamic equilibrium of Si-O bonds.
It realizes more stable in-situ polymerization of the lithium-ion battery interface, has self-healing capabilities, inhibits the growth of lithium dendrites, ensures the safe and stable operation of the battery, and has a simple production process and excellent electrochemical performance.
Smart Images

Figure BDA0005160797640000021 
Figure BDA0005160797640000032 
Figure BDA0005160797640000033
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a room temperature, green, and in-situ polymerized self-repairing polysilazane gel electrolyte. Technical Background
[0002] Traditional liquid electrolytes have poor compatibility with lithium metal anodes during the cycle, and are prone to problems such as lithium dendrites piercing the diaphragm. Gel electrolyte is a network structure with good stability and cohesion, which can wrap organic liquids in it, thereby reducing the risk of organic liquid leakage; in addition, the properties of gel semi-solid elastomers give it certain mechanical strength and processability, which can inhibit the growth of lithium dendrites at the interface and can be used in the field of flexible energy storage.
[0003] CN202310475209.2 A dual-continuous phase gel polymer electrolyte, its preparation method and application, ether small molecule plasticizers, lithium salts, amine monomers and epoxy monomers are mixed to obtain a raw material mixture, and the diaphragm is placed therein for in-situ compounding, wherein the amine monomers and epoxy monomers containing benzene rings or cyclohexyl rigid rings react rapidly under conditions of lithium salt catalysis acceleration to construct a rigid cross-linked network. The formed gel electrolyte is a rigid structure and does not have self-healing properties. 202110412045.X Self-healing polymer electrolyte membrane and its preparation method and battery, which prepares a self-healing polymer electrolyte membrane by polyamines and polyethylene glycol diglycidyl ether. It does not contain Si-O bonds, and the prepared electrolyte membrane is not in line with the gel electrolyte, and the production conditions are complicated, requiring the use of ice bath conditions. And all of the above are non-in-situ polymerization methods to form gel electrolytes.
[0004] The in-situ polymerization method uses liquid gel electrolyte to assemble the battery, and directly polymerizes inside the battery through chemical crosslinking and thermal induced polymerization. This method keeps Li + The conductivity is improved and the interface stability is better. Therefore, in-situ polymerization is a relatively preferred choice for gel electrolytes.
[0005] In summary, it is of great significance to develop a room temperature, green and in-situ polymerization method for preparing self-healing polysilazane gel electrolyte. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies in the prior art. The present invention proposes a method for preparing a self-healing polysilazane gel electrolyte that is room temperature, green, and polymerized in situ, which can simultaneously meet the conditions of in-situ polymerization, self-healing, no need for heating, and organic solvent-free volatilization. The present invention uses epoxy monomers or amine monomers containing Si-O bonds, which form a cross-linked network through amine monomers and epoxy monomers. The unique dynamic balance between Si-O bonds gives the gel electrolyte the ability to self-heal, which can well inhibit the growth of lithium dendrites. The in-situ polymerization method used makes the interface more stable, thereby achieving safe and stable operation of lithium metal batteries. In addition, the present invention also has the advantages of simple production process, excellent electrochemical performance, ability to match high-voltage positive electrodes, and solvent-free volatilization.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The steps include:
[0009] S1: adding a glycidyl ether monomer and an amine monomer containing a Si-O bond; or adding a glycidyl ether monomer and an amine monomer containing a Si-O bond to a corresponding solvent in a ratio of epoxy group to amino group of 1:1, and stirring to obtain a uniform and transparent liquid A; wherein at least one of the glycidyl ether monomer or the amine monomer contains a silicon-oxygen bond;
[0010] S2: adding lithium salt and initiator to the uniform transparent liquid A to obtain a uniform transparent liquid B, i.e., a gel electrolyte liquid;
[0011] S3: Place the uniform and transparent liquid B at room temperature and polymerize it for a period of time to obtain a gel electrolyte. According to the present invention, preferably, the glycidyl ether monomer is characterized by containing two or more terminal ethylene oxides, which include but are not limited to the following structures:
[0012]
[0013] According to the present invention, preferably, the glycidyl ether monomer containing Si-O bonds includes but is not limited to the following structure: According to the present invention, preferably, the amine monomer includes but is not limited to the following structure:
[0014]
[0015] According to the present invention, preferably, the amine monomer containing Si-O bonds includes but is not limited to the following structure:
[0016]
[0017] Preferably, the initiator used is LiBF4 or FEC.
[0018] Preferably, the concentration of LiBF4 or FEC initiator is 0.01-3 mol / L.
[0019] Preferably, the solvent used is one or a mixture of DEC, EMC, DME, EC, EMC, DMC, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether; different solvents can dissolve different amounts of lithium salts, and ether solvents are preferred in the present invention.
[0020] Preferably, the lithium salt is one or a mixture of LiPF6, LiTFSI, LiBF4 and LiODFB.
[0021] Preferably, the concentration of the lithium salt is 0.01-4 mol / L.
[0022] Preferably, the glycidyl ether monomers and amine monomers account for 1-50% of the total weight of the gel electrolyte (ie, the solid content of the glycidyl ether monomers and amine monomers is 1-50%). More preferably, the solid content is 20%-50%. Most preferably, the solid content is 20%.
[0023] Preferably, the polymerization time is 1-120 h.
[0024] Preferably, the application field of the gel electrolysis for lithium-ion batteries is lithium-ion batteries.
[0025] Preferably, the glycidyl ether monomer and amine monomer solution system in the self-healing polysilazane gel electrolyte is polymerized between the positive and negative electrodes in an in-situ polymerization manner to form a gel electrolyte.
[0026] Specific application of gel electrolyte in battery: Battery assembly process: In a glove box filled with argon environment, cellulose membrane is used as a diaphragm, and the prepared gel electrolyte liquid is dripped on the diaphragm to assemble button cells with the positive and negative electrodes. Let it stand for polymerization at room temperature, and the battery will be in situ polymerized into a gel polymer electrolyte supported by a cellulose membrane. Preferably, the negative electrode material of the lithium-ion battery is lithium metal, graphite, silicon, and silicon-carbon composite materials. The positive electrode material of the lithium-ion battery is LiCoO2, LiFePO4, and ternary materials.
[0027] Compared with the prior art, the beneficial effects of the present invention are: it adopts an in-situ polymerization method with smaller and more stable interface internal resistance; the self-healing ability formed can inhibit the growth of lithium dendrites; there is no solvent volatilization, no need for heating, and the operation is simple and easy; it has the ability to match the high-voltage positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are optical polymerization state images of gel electrolytes with different solid contents in Example 1.
[0029] Figure 2These are the aggregation state images at different time periods in Example 1.
[0030] Figure 3 Infrared spectra of the gel electrolyte and DME solvent of Example 1
[0031] Figure 4 The electrochemical impedance spectra at different temperatures (a) and the conductivity properties at different temperatures (b) in Example 1.
[0032] Figure 5 Test of the self-healing performance of gel electrolyte.
[0033] Figure 6 LSV test in gel electrolyte.
[0034] Figure 7 To test the cycle and rate performance of the battery.
[0035] Figure 8 Electrochemical impedance spectra of electrolytes with different solid contents (a) and ionic conductivity of electrolytes with different solid contents (b).
[0036] Fig. 9 Schematic diagram of the in-situ polymerization of gel electrolyte between the positive and negative electrodes of the battery. DETAILED DESCRIPTION
[0037] The technical scheme and effects of the present invention are further described below in conjunction with embodiments; however, the specific methods, formulations and descriptions used are not limitations of the present invention.
[0038] In the following embodiments, the model of the stainless steel battery shell is CR2032.
[0039] Example 1: 0.6 g of 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and 0.1 g of anhydrous piperazine were added to the corresponding 2.8 g of DME electrolyte, the amount of polymer monomer in the whole gel electrolyte was 20%, and stirred evenly for 1 hour; then 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 0.5 g of lithium tetrafluoroborate were added, and stirred evenly for 1 hour to obtain a gel electrolyte liquid; finally, 60 μl of a transparent and clear gel electrolyte liquid was dripped into the battery. After standing at room temperature for 3 days, the inside of the battery was a gel polymer electrolyte supported by a cellulose membrane.
[0040] Based on the above method steps, gel electrolyte liquids were prepared with glycidyl ether monomers and amine monomers accounting for 10%, 30%, and 40% of the total weight of the gel electrolyte, and then polymerized to see whether the gel electrolyte can be polymerized. Figure 1As shown, the optical polymerization state images of the gel electrolytes with different solid contents provided in this embodiment 1 show that when the solid content of the polymer monomer is not less than 20%, the gel electrolytes can be solidified, while it is difficult to polymerize the gel electrolytes below 20%, which illustrates the feasibility of the gel polymer electrolyte of this scheme.
[0041] Figure 8 The electrochemical impedance spectra of gel electrolytes with different solid contents are shown in Figure 2. After calculation, the conductivity of gel electrolytes with solid contents of 20%, 30%, and 40% are 0.153mS / cm, 0.074mS / cm, and 0.025mS / cm, respectively. Considering that battery operation requires higher ionic conductivity, subsequent battery tests were conducted using gel electrolytes with a solid content of 20%.
[0042] like Figure 2 As shown, the images of the polymerization state of the gel electrolyte liquid at different time periods provided in this embodiment 1 are not difficult to see that the liquid before curing is slightly green and transparent, with very low viscosity and fluidity; in the intermediate state of curing, the color of the gel electrolyte turns brown and has a certain viscosity; when the curing is complete, the color of the gel electrolyte is dark brown and does not flow when inverted. In summary, the configured gel electrolyte has the feasibility of in-situ polymerization.
[0043] like Figure 3 The following are infrared spectra of gel electrolyte and DME solvent. The black infrared spectrum corresponds to DME solvent, which is taken from the infrared spectrum library; the red infrared spectrum corresponds to the polymerized gel electrolyte, which uses the total reflection infrared spectrum mode. By comparison, it can be found that DME solvent exists in the gel electrolyte; 1095cm -1 The corresponding Si-O-Si infrared absorption peaks are derived from 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane, which are consistent with the gel electrolyte formula. In the infrared test, the corresponding position of the infrared absorption peak of the R-NH-R1 secondary amine after piperazine is dissolved in the solvent is 3310-3350cm -1 , it can be found through observation that the infrared peak corresponding to this point in the gel electrolyte is weak, indicating that the degree of polymerization is relatively complete. Figure 4 As shown, the conductivity of the gel polymer electrolyte supported by the cellulose membrane at different temperatures measured by the battery in Example 1. At room temperature, the conductivity of the gel electrolyte can reach 0.2 mS / cm, indicating that the gel electrolyte has high conductivity.
[0044] like Figure 5 As shown in FIG. 1 , the self-healing performance test of the gel electrolyte in Example 1 is shown. After the gel electrolyte is broken, it can recover to its original state within a period of time (within 2-5 hours), indicating that it has good self-healing ability. Figure 6As shown, it is the LSV test in the gel electrolyte in this embodiment 1. It can be seen that the decomposition voltage of the basic electrolyte is about 4.5V, while the double decomposition voltage of the gel electrolyte reaches more than 5V, which indicates that the prepared gel electrolyte has the ability to match the high-voltage positive electrode.
[0045] The specific application of the gel electrolyte prepared in Example 1 in the battery is described as follows: Battery assembly process: In a glove box filled with argon, the LFePO4 pole piece or NCM811 pole piece prepared above is used as the positive electrode, the lithium sheet is used as the negative electrode (diameter is 15.6 mm), and the cellulose film (TBL4825) is used as the separator (25 micron thickness), 60 μL of the gel electrolyte liquid prepared above is added dropwise, and CR2023 button batteries are used for assembly. After being left at room temperature for 3 days, the gel electrolyte is polymerized in situ inside the battery.
[0046] The production process of the NCM811 pole piece is as follows: first prepare PVDF glue with a solid content of 6%, then mix the positive electrode active material, conductive carbon black and PVDF (PVDF glue of corresponding mass in the actual process) at a solid ratio of 96:2:2, and finally add an appropriate amount of NMP solvent to adjust the viscosity of the slurry to a suitable range. The mixed slurry is evenly coated on aluminum foil, dried at 80°C for 3 hours, and then cut into positive pole pieces with a diameter of 12mm, then transferred to a vacuum drying oven at 120°C for 12 hours, and placed in a high-purity argon glove box for standby use. Before use, compact and dry again for 12 hours.
[0047] The production process of LiFePO4 pole piece: first prepare PVDF glue with a solid content of 6%, then mix the positive electrode active material, conductive carbon black and PVDF (PVDF glue of corresponding mass in the actual process) in a solid ratio of 8:1:1, and finally add an appropriate amount of NMP solvent to adjust the viscosity of the slurry to a suitable range. The mixed slurry is evenly coated on aluminum foil, dried at 80°C for 3 hours, and then cut into positive pole pieces with a diameter of 12mm, then transferred to a vacuum drying oven at 120°C for 12 hours, and placed in a high-purity argon glove box for standby use. Before use, it is compacted and dried again for 12 hours.
[0048] like Figure 7 As shown, the LiFePO4 and LiNi provided in this embodiment 1 0.8 Co 0.1 Mn 0.1 Cycle and rate performance of O2 batteries.
[0049] According to the test, in the LiFePO4||Li battery, at a current density of 1C, the initial capacity is 143mAh / g, and after 200 cycles, the capacity retention rate of the battery can reach about 90%, and at a current density of 5C, the discharge specific capacity reaches 120mAh / g;
[0050] In LiNi 0.8 Co 0.1 Mn 0.1 In the O2||Li battery, at a current density of 1C, the capacity retention rate of the battery can reach about 75% after 280 cycles, and at a current density of 2C, the discharge specific capacity reaches 105mAh / g; this shows that the gel electrolyte has excellent electrochemical properties and high voltage resistance.
[0051] Embodiment 2:
[0052] 0.7 g of 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and 0.2 g of propargylamine were added to the corresponding tetraethylene glycol dimethyl ether, the amount of the polymer monomer in the entire gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 0.5 g of lithium tetrafluoroborate were added, and the mixture was stirred evenly for 1 hour to obtain a gel electrolyte liquid; 60 μl of the transparent and clear gel electrolyte liquid was dripped into a cellulose membrane, and a button battery was assembled. After being left for a period of time, the battery was polymerized into the gel electrolyte.
[0053] The conductivity of the gel electrolyte prepared in Example 2 is 0.22 mS / cm.
[0054] The assembly method of the LiFePO4||Li battery is the same as that of Example 1. In the LiFePO4||Li battery, at a current density of 1C, the first cycle discharge capacity is 142mAh / g, and the capacity retention rate of the battery can reach about 85% after 200 cycles.
[0055] Embodiment 3:
[0056] 0.55 g of 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and 0.15 g of n-butylamine were added to DME, the amount of polymer monomer in the whole gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.75 g of lithium bis(trifluoromethanesulfonyl)imide and 0.35 g of lithium difluorooxalatoborate were added, and the mixture was stirred evenly for 1 hour to obtain a gel electrolyte liquid; finally, 60 μl of the transparent and clear gel electrolyte liquid was dripped into a cellulose membrane and assembled into a button cell, and after being left for a period of time, the inside of the cell was polymerized into the gel electrolyte.
[0057] The conductivity of the gel electrolyte prepared in Example 3 is 0.12 mS / cm.
[0058] The assembly method of the LiFePO4||Li battery is the same as that of Example 1. In the LiFePO4||Li battery, at a current density of 1C, the first cycle discharge specific capacity is 141 mAh / g, and the capacity retention rate of the battery can reach about 70% after 200 cycles.
[0059] Embodiment 4:
[0060] 0.45 g of pentaerythritol glycidyl ether and 0.15 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added to the corresponding DME, the amount of the polymer monomer in the entire gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.75 g of lithium bistrifluoromethanesulfonyl imide and 0.35 g of lithium tetrafluoroborate were added, and the mixture was stirred evenly for 1 hour to obtain a gel electrolyte liquid; finally, 60 μl of the transparent and clear gel electrolyte liquid was dripped into a cellulose membrane, and a button battery was assembled. After being left for a period of time, the battery was polymerized into the gel electrolyte.
[0061] The conductivity of the gel electrolyte prepared in Example 4 is 0.24 mS / cm.
[0062] The assembly method of the LiFePO4||Li battery is the same as that of Example 1. In the LiFePO4||Li battery, at a current density of 1C, the first cycle discharge capacity is 138mAh / g, and the capacity retention rate of the battery can reach about 88% after 200 cycles.
[0063] Embodiment 5:
[0064] 0.75 g of 4,4'-biphenyl bisphenol diglycidyl ether and 0.13 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added to 2 g of DEC, the amount of the polymer monomer in the entire gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.75 g of lithium bistrifluoromethanesulfonyl imide and 0.35 g of lithium hexafluorophosphate were added, and the mixture was stirred evenly for 1 hour to obtain a gel electrolyte liquid; 60 μl of the transparent and clear gel electrolyte liquid was dripped into a cellulose membrane, and a button battery was assembled. After being left for a period of time, the battery was polymerized into the gel electrolyte.
[0065] The conductivity of the gel electrolyte prepared in Example 5 is 0.34 mS / cm. In a LiFePO4||Li battery (the battery assembly method is the same as in Example 1), at a current density of 1C, the battery capacity retention rate can reach about 78% after 200 cycles.
[0066] The gel electrolytes prepared in Examples 2-5 were tested for self-healing performance using the same testing method as in Example 1. After the gel electrolytes were broken, they could all recover to their original state within a period of time (2-5 hours), indicating that the gel electrolytes prepared in Examples 2-5 had good self-healing capabilities.
[0067] Comparative Example 1:
[0068] 0.65 g of pentaerythritol glycidyl ether and 0.1 g of anhydrous piperazine were added to the corresponding DME electrolyte, the amount of the polymer monomer in the entire gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 0.5 g of lithium tetrafluoroborate were added, and the mixture was stirred evenly for 1 hour to obtain a gel electrolyte liquid; finally, 60 μl of the transparent and clear gel electrolyte liquid was dripped into a cellulose membrane, and a button cell was assembled. After being left at room temperature for 3 days, the gel electrolyte was polymerized inside the cell.
[0069] The conductivity of the gel electrolyte prepared in Comparative Example 1 is 0.05mS / cm. In the LiFePO4||Li battery, at a current density of 1C, the first cycle discharge capacity is 112mAh / g, and the capacity retention rate of the battery can reach about 73% after 200 cycles. By comparing Example 1 with Example 4, due to the absence of Si-O bonds, the polymer system does not have self-healing properties. It can also be seen that the presence of Si-O bonds also has an impact on the electrochemical performance.
[0070] Comparative Example 2:
[0071] 0.6 g of 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and 0.1 g of anhydrous piperazine were added to the corresponding DME electrolyte, the amount of polymer monomer in the whole gel electrolyte was 20%, and the mixture was stirred evenly for 1 hour; then 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 0.5 g of lithium tetrafluoroborate were added, and the mixture was stirred evenly for 1 hour; finally, 60 μl of transparent and clear gel electrolyte liquid was dripped into the cellulose membrane, and a button battery was assembled. After heating at 60° C. for polymerization reaction, the gel electrolyte was polymerized inside the battery.
[0072] The assembly method of LiFePO4||Li battery is the same as that of Example 1. Compared with Example 1, the capacity retention rate of the battery of Comparative Example 2 after 200 cycles is greatly reduced compared with that of Example 1. This is because the heating polymerization of Comparative Example 2 will lead to reduced solvent volatilization, so that the cycle performance of the battery will be significantly attenuated.
[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization, characterized in that: (1) adding a glycidyl ether monomer and an amine monomer into a solvent at a molar ratio of epoxy group to amino group of 1:1, stirring, and obtaining a uniform and transparent liquid A; wherein at least one of the glycidyl ether monomer and the amine monomer contains a silicon-oxygen bond; and the glycidyl ether monomer contains two or more terminal ethylene oxides; (2) adding lithium salt and initiator to the uniform transparent liquid A to obtain a uniform transparent liquid B, which is a gel electrolyte liquid; (3) Liquid B is polymerized at room temperature to obtain a self-healing polysilazane gel electrolyte.
2. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The glycidyl ether monomer structure is one of the following:
3. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The amine monomer is one of the following:
4. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The initiator is LiBF4 or FEC; the concentration of the initiator is 0.01-3 mol / L.
5. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The solvent is one or a mixture of DEC, EMC, DME, EC, EMC, DMC, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
6. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The concentration of lithium salt is 0.01-4 mol / L.
7. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The glycidyl ether monomers and amine monomers account for 20-50% of the total weight of the gel electrolyte.
8. The method for preparing a self-healing polysilazane gel electrolyte by in-situ polymerization according to claim 1, characterized in that: The room temperature polymerization time is 1-120h.
9. Application of the self-healing polysilazane gel electrolyte prepared by the method according to any one of claims 1 to 8 in lithium-ion batteries, characterized in that: The self-healing polysilazane gel electrolyte is polymerized between the positive and negative electrodes of the lithium-ion battery in an in-situ polymerization manner to form a gel electrolyte.
10. The use according to claim 9, wherein the prepared gel electrolyte liquid is dripped onto the diaphragm, and then assembled into a battery with the positive electrode and the negative electrode, and polymerized at room temperature, and the gel electrolyte is polymerized in situ inside the battery.
Citation Information
Patent Citations
Bicontinuous phase gel polymer electrolyte as well as preparation method and application thereof
CN116505064A
Self-repairing polymer electrolyte membrane, preparation method thereof and battery
CN113193235A
Battery preparation method using in-situ polymerization interface self-repairing polymer electrolyte
CN118367224A
Gel Electrolyte, Preparing Method Thereof, Gel Electrolyte Battery, and Preparing Method Thereof
US20140050990A1
Polymer electrolytes for dendrite-free energy storage devices having high coulombic efficiency
US20150056488A1
Cited By
Wide-temperature-range semi-solid electrolyte as well as preparation method and application thereof
CN120473562A